2005
DOI: 10.1097/01.wnp.0000158948.00901.4e
|View full text |Cite
|
Sign up to set email alerts
|

Excitability of Spinal Inhibitory Circuits in Patients with Spasticity

Abstract: The excitability of Ia inhibition and D1 inhibition after stimulation of the common peroneal nerve to the soleus motoneuron pool was investigated in 37 spastic patients at rest and onset of voluntary ankle dorsiflexion. Ia inhibition was determined as the short-latency depression of the soleus H-reflex and D1 inhibition as the long-latency depression. There was no significant difference in Ia inhibition between the paraplegic and control groups, however Ia inhibition in the hemiplegic group was significantly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…We found that the Sol H‐reflex was suppressed by deep peroneal nerve stimulation at C‐T stimulus intervals between 1.0 and 3.0 msec. This finding was consistent with previous studies (3,5,6,11). The timing of short‐latency inhibition was comparable with disynaptic Ia inhibition.…”
Section: Discussionsupporting
confidence: 93%
“…We found that the Sol H‐reflex was suppressed by deep peroneal nerve stimulation at C‐T stimulus intervals between 1.0 and 3.0 msec. This finding was consistent with previous studies (3,5,6,11). The timing of short‐latency inhibition was comparable with disynaptic Ia inhibition.…”
Section: Discussionsupporting
confidence: 93%
“…Modulation of Ia PSI by rhythmic activity in cervical spinal cord oscillators is an important mechanism for reflex modulation in the legs in response to arm cycling [3,22]. This mechanism appears partially preserved after stroke [34,35], although participants with stroke have difficulty in modulating the excitability of inhibitory pathways in different motor tasks [76,77,78]. However, given the involvement of the fusimotor system on excitability in the stretch reflex pathway [79,80], changes in gamma bias related to changes in supraspinal regulation could also have contributed to changes in MA SOL stretch reflex excitability.…”
Section: Discussionmentioning
confidence: 99%
“…A malfunction in some spinal pathways responsible for controlling the excitability of the stretch reflex has been associated with the development of spasticity in conditions such as following stroke and spinal cord injury. For instance, reduced PSI of Ia terminals [ 64 67 ] has been reported for these patients as compared to healthy controls. As weak steady contractions of spastic muscles may be used in the early stages of rehabilitation programs designed to recover/maintain function in these patients, the results of the present study suggest that it would be preferable to use protocols relying on isometric (FTs) rather than on anisometric (PTs) contractions, so as to favor recovery of lost spinal inhibition (specifically PSI) by training contractions under higher excitability of the primary afferent depolarization interneurons mediating PSI of Ia afferents.…”
Section: Discussionmentioning
confidence: 99%